Ethnopharmacology of Boraginaceae Family- An Update - Siva Krishnan (Journal of Global Pharma Technology, 2019)
Ethnopharmacology studies natural medicines derived from plants and other substance that have been traditionally used by group of people to treat various human diseases. In this world, there is a dynamic relationship between plants and humans. Traditionally the plants used to cure diseases are termed as medicinal plants. Boraginaceae, the borage- or forget-me-not family, includes a variety of shrubs, trees, and herbs, totaling about 2,400 species in 146 genera found worldwide. It is effective against a variety of diseases like hepatic, cardiovascular, cancer, urolithiasis, baldder, respiratory, leprosy, syphilis, gonorrhea, aphthous ulcers, rheumatism, spleen and lung. This review reveals the traditional medicinal values of the Boraginaceae family and it will be helpful to explore the knowledge about Boraginaceae species for the researchers.